2022
DOI: 10.1002/jmrs.641
|View full text |Cite
|
Sign up to set email alerts
|

Understanding reasons for image rejection by radiologists and radiographers

Abstract: Introduction: A core element of a radiographer's role is the decision on whether a radiograph is sufficient for diagnosis, or a repeat examination is needed. Studies illustrate the disagreement on the diagnostic value of radiographs between radiographers and radiologists, which may influence repeat examinations. This study investigates if parameters contributing to image quality are possible determinants to explain the difference between professions. Methods: A total of 74 radiographers and radiologists from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…It is suggested that more emphasis is now placed on repeating for perfection rather than clinical acceptability 3 . This ease of image rejection comes with the burden of greater patient dose, 4 particularly rejection of an image that is considered diagnostically acceptable 5 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is suggested that more emphasis is now placed on repeating for perfection rather than clinical acceptability 3 . This ease of image rejection comes with the burden of greater patient dose, 4 particularly rejection of an image that is considered diagnostically acceptable 5 …”
Section: Introductionmentioning
confidence: 99%
“…The difference is exacerbated when comparing the decisions on image acceptability between radiographers and radiologists. Studies demonstrate large discrepancies between images rejected by radiologists and radiographers, 5,10 with radiologists being up to 46% less likely to repeat images compared to radiographers 10 . Moreover, one study reports that radiologists are likely to accept up to 50% more images with positioning errors than radiographers 11 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the radiographer's assessment of image quality, radiologists tend to differ with variable tolerances of image quality acceptability. In this edition of JMRS, Decoster et al 5 conducted a multisite study involving three countries that sought to explore the difference between radiographers and radiologists based on their judgement on the quality of a radiograph. They found that radiographers were more critical in their assessment of radiographs compared to radiologists.…”
mentioning
confidence: 99%